2018
DOI: 10.1016/j.omtn.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as Predictive Biomarkers of Type 2 Diabetes Mellitus Development in Coronary Heart Disease Patients from the CORDIOPREV Study

Abstract: Circulating microRNAs (miRNAs) have been proposed as type 2 diabetes biomarkers, and they may be a more sensitive way to predict development of the disease than the currently used tools. Our aim was to identify whether circulating miRNAs, added to clinical and biochemical markers, yielded better potential for predicting type 2 diabetes. The study included 462 non-diabetic patients at baseline in the CORDIOPREV study. After a median follow-up of 60 months, 107 of them developed type 2 diabetes. Plasma levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 58 publications
(82 reference statements)
2
84
0
1
Order By: Relevance
“…miRNAs have been proposed as surrogate markers of the prediabetes state, 38,39 diabetes and cardiovascular complications, 40 being detectable in a stable form in blood circulation and biological fluids. Many studies have revised the involvement of miRNAs in the vascular complications of diabetes 29 as well as in atherosclerosis, 41 determining a branch of investigation deserving special attention due to potential diagnostic and therapeutic implications.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…miRNAs have been proposed as surrogate markers of the prediabetes state, 38,39 diabetes and cardiovascular complications, 40 being detectable in a stable form in blood circulation and biological fluids. Many studies have revised the involvement of miRNAs in the vascular complications of diabetes 29 as well as in atherosclerosis, 41 determining a branch of investigation deserving special attention due to potential diagnostic and therapeutic implications.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In addition to diagnosing DR through histological examination of the fundus vasculature, circulating miRNAs were found to play critical roles in DR development, suggesting that miRNAs could also serve as new biomarkers in detecting or predicting the progress of retinopathy and furthermore, the overall progress of DM [139][140][141]. Analysis of circulating miRNAs from serum or plasma samples of DM patients both with and without DR showed altered expression levels of many miRNAs throughout different patient populations (e.g., ages, type of DM, years after onset, etc.,) [142].…”
Section: Mirnas In Drmentioning
confidence: 99%
“…Lv et al identified a correlation between serum miR‐130b level changes and the severity of DN . Jimenez et al proposed a new model (9 miRNAs + Finnish Diabetes Risk Score + HbA1C) that use both HbA1C and miRNA to improve sensitivity and specificity and increase the predictive value of developing DM …”
Section: Possible Associated Mechanism Between Mirnas and Dmmentioning
confidence: 99%